2007
DOI: 10.1038/sj.jp.7211640
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing enterocolitis associated with in utero and breast milk exposure to the selective serotonin reuptake inhibitor, escitalopram

Abstract: A term neonate presenting with necrotizing enterocolitis following in utero and breast milk exposure to the newest serotonin selective reuptake inhibitor, escitalopram, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Potts et al l(21) reported an case of necrotizing enterocolities (NEC) on the fifth postnatal day in a term neonate exposed to escitalopram (20 mg daily) in utero and during breastfeeding. The mother continued taking escitalopram and discontinued breastfeeding.…”
Section: Selective Serotonin-reuptake Inhibitors (Ssri)mentioning
confidence: 99%
“…Potts et al l(21) reported an case of necrotizing enterocolities (NEC) on the fifth postnatal day in a term neonate exposed to escitalopram (20 mg daily) in utero and during breastfeeding. The mother continued taking escitalopram and discontinued breastfeeding.…”
Section: Selective Serotonin-reuptake Inhibitors (Ssri)mentioning
confidence: 99%
“…Such alterations in the mucosal-derived serotonin contribute to intestinal dysmotility (48) and have been associated with inflammatory bowel disease (75). Importantly, NEC has been associated with maternal use of selective serotonin reuptake inhibitors during pregnancy (76).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, knockout of SERT, which increases 5‐HT effects by decreasing its reuptake and metabolism, leads to increased NEC inflammation . Although SERT inhibitors (SSRI) are commonly used during pregnancy and lactation, and various behavioral and pulmonary effects on the neonate have been described, only very limited data suggest a link between maternal SSRI use and NEC …”
Section: Implications For Neurogastroenterologymentioning
confidence: 99%